Improved detectability in pharmacokinetic study of tibolone by gas chromatography-high resolution mass spectrometry with selected ion monitoring - Son, Junghyun; Moon, Ju-Yeon; Kim, Seol-A; Cho, Young-Dae; Kim, Jong-Dae; Kim, Dong-Hyun; Choi, Man Ho (ELSEVIER SCIENCE BV, 2006)
A combination of high resolution mass spectrometry (HRMS) and gas chromatography has been used to improve sensitivity and selectivity in pharmacokinetic stud), of tibolone. The study was undertaken in 12 healthy volunteers after oral administration of 2.5 mg tibolone tablet and plasma concentrations of two major metabolites, 3 alpha-hydroxytibolone (3 alpha OHT) and 3 beta-hydroxytibolone (3 beta OHT), were analyzed first by gas chromatography-mass spectrometry (GC-MS). Pharmacokinetic parameters AUC(0-12h) (13.70 +/- 4.01 ng h ml(-1)), Cm, (3.89 +/- 1.00 ng ml-1), and T-max (1.83 +/- 0.55h) for 3 alpha OHT were initially measured by GC-MS. The AUC(0-12h) of 3 beta OHT concentration was 5.5-folds higher than that of 3(alpha OHT. Improved results in delectability were obtained by GC-HRMS analysis of two metabolites with the same samples. The previously undetected metabolites, 3(alpha OHT and 3POHT, in samples collected at 15 and 24h in GC-MS system were successfully detected by GC-HRMS analysis and could be calculated pharmacokinetic parameters as well. But, no significant pharmacokinetic parameters were found in two analytical runs. The limit of quantification for HRMS analysis in selected ion monitoring mode of 3 alpha OHT and 3 beta OHT as trimethylsilyl derivatives down to 0.02 ng ml(-1). while their recovery rates varied in the range of 82.5-108.0%. This method demonstrated a good overall accuracy and precision as 90.1-102.3% and 1.6-11.4%, respectively. This method could potentially have implications for pharmacokinetic study or clinical trial of rapidly metabolized drugs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: IN-VIVO; POSTMENOPAUSAL WOMEN; TESTOSTERONE; METABOLISM; HAIR